2021
DOI: 10.3390/children8040258
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Initiation of Alcohol Drinking among Elementary and Kindergarten Students

Abstract: Parental experience of initiation of alcohol drinking has been identified as one of the early causes of alcohol drinking in preadolescents in many countries, including Japan. This study identified the association between parental alcohol-related knowledge and the initiation of alcohol use among preadolescent students in an urban area in Japan. Self-administrated questionnaires were distributed to 420 parents of kindergarteners and elementary school students, of which 339 were filled and returned (response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Children who live in alcoholic families adopt the behavioral patterns of their parents. Children whose parents consume alcohol frequently start drinking alcohol very early (Aiken et al, 2022;Eto and Sugimoto, 2021). Our research has shown that children aged 15-17 fully adopt their parents' behavior patterns.…”
Section: Table 5 the Relationship Between Availability Of Alcohol To ...mentioning
confidence: 67%
“…Children who live in alcoholic families adopt the behavioral patterns of their parents. Children whose parents consume alcohol frequently start drinking alcohol very early (Aiken et al, 2022;Eto and Sugimoto, 2021). Our research has shown that children aged 15-17 fully adopt their parents' behavior patterns.…”
Section: Table 5 the Relationship Between Availability Of Alcohol To ...mentioning
confidence: 67%